IMPLEMENTASI ANALISIS RANTAI NILAI DI SEKOLAH DASAR NEGERI (SDN) CIJAMBU 1 - Maryam, Iyam Siti; Khofifah, Juliani Musti; Kurniatun, Taufani Chusnul (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to analyze the value chain implementation at SD Negeri Cijambu 1 as a strategy to improve the quality of educational services. Using a qualitative approach, the research identifies primary and supporting activities that create added value. The findings indicate that implementing the Merdeka Curriculum, integrating local values, and strengthening school culture have supported holistic student competency development. However, challenges such as limited facilities, a relatively small number of students, and suboptimal use of technology remain obstacles. Strategies to enhance added value include diversifying locally-based extracurricular programs, optimizing technology in learning and administration, and fostering closer collaboration with stakeholders. By addressing these challenges, SD Negeri Cijambu 1 can strengthen its competitiveness and positively impact students and the community.